2013
DOI: 10.3791/4267
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Skeletal Muscle Tissues from Murine Myoblast Progenitor Cells and Application of Electrical Stimulation

Abstract: Engineered muscle tissues can be used for several different purposes, which include the production of tissues for use as a disease model in vitro, e.g. to study pressure ulcers, for regenerative medicine and as a meat alternative 1 . The first reported 3D muscle constructs have been made many years ago and pioneers in the field are Vandenburgh and colleagues 2,3 . Advances made in muscle tissue engineering are not only the result from the vast gain in knowledge of biochemical factors, stem cells and progenitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…In monolayer culture, various studies on the relationship between alignment and electrical load have been reported [3][4][5][6][7][8]10]. Hinkle and colleagues showed that initially spherical myoblasts formed bipolar axes at right angles to an applied electrical field [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In monolayer culture, various studies on the relationship between alignment and electrical load have been reported [3][4][5][6][7][8]10]. Hinkle and colleagues showed that initially spherical myoblasts formed bipolar axes at right angles to an applied electrical field [3].…”
Section: Discussionmentioning
confidence: 99%
“…In monolayer culture, the application of a direct current (DC) electrical field to muscle cells causes myoblast axes to orient perpendicular to the electrical current [3][4][5][6][7][8]. However, it has not been determined if skeletal muscle cells will align in a 3D collagen gel culture using a similar electrical load.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to mechanical stimulation, electrical stimulation, used to mimic neuronal input to muscle, has also been shown to promote cell alignment, enhance fusion, improve maturation, and even guide fast-to-slow fiber type switching in engineered muscle [76-78]. Systems designed for exogenous electrical stimulation typically apply graphite, stainless steel, or platinum electrodes parallel to the engineered muscle within the culture dish to induce a field shock [76-79]. …”
Section: Engineering Functional Muscle Constructsmentioning
confidence: 99%
“…However, an ability to maintain such cells in configurations which facilitate assessment of their contractile output has proved more difficult. While the seeding of myocytes within three-dimensional scaffolds has alleviated this issue to a degree (Dennis and Kosnik, 2000; Dennis et al, 2001; Langelaan et al, 2011; Rhim et al, 2010; Rhim et al, 2007; Sakar et al, 2012; Smith et al, 2012; van der Schaft et al, 2013; Vandenburgh, 2010; Weist et al, 2013), the ability to investigate skeletal muscle contraction at the single myotube level in a reliable and reproducible manner remains problematic. Moreover, many 3D models rely on visual interrogation in order to measure contractile activity, which can make accurate assessment of contraction profiles challenging (Agarwal et al, 2013; Sakar et al, 2012; Vandenburgh et al, 2008).…”
mentioning
confidence: 99%